Squamous cell carcinoma of the stomach: focus on a heterogeneous disease at diagnosis. Case report and literature review - Monti, Manlio; Limarzi, Francesco; Oboldi, Devil; Sbrancia, Monica; Pallotti, Maria Caterina; Miserocchi, Giulia; Ghini, Virginia; Zanuccoli, Sofia; Cagnazzo, Sara; Frassineti, Giovanni Luca (Frontiers in Oncology, 2024)
Primary squamous cell carcinoma (SCC) can originate in different parts of the body, including the head, neck, lung, bronchus, cervix uteri, esophagus, and cardia, and subsequently metastasize to the stomach. Primary gastric squamous cell carcinoma (GSCC) is a rare disease. To better understand GSCC, we present the case of a 72-year-old woman with a primary GSCC. A chest and abdominal CT scan highlighted a 36×26 mm mass with a 41 mm longitudinal diameter, which included the origin of the celiac tripod. The disease appeared to originate exophytically from the gastric wall. An ultrasound-endoscopy showed a hypoechoic formation with not well-defined margins measuring 40×30 mm involving the origin of the celiac tripod, about 10 mm from the gastric wall. An endoscopic fine-needle aspiration showed a poorly differentiated carcinoma. A PET/CT scan showed a hyperaccumulation of the known expansive formation at the celiac tripod (SUV 11.9) without specific cleavage planes from the stomach. A gastroscopy showed a regular esophagus and an absence of gastric protruding lesions. In the subcardial area, on the posterior wall, there was a slightly raised sub-centimetric area covered by bleeding mucosa where the biopsy had been performed. The pathological report showed chronic gastritis. An eco-endoscopy confirmed a hypoechoic neoformation measuring 30×40 mm that appeared to originate from the muscular layer of the gastric wall. The biopsy report was positive for broad-spectrum cytokeratins (AE1/AE3), CK5/6/7, p40, p63 and negative for CK20, PAS, TTF-1, anti-smooth muscle actin, CD45 (LCA), ERG, and S100. The clinical picture suggested poorly differentiated carcinoma with squamous differentiation. We analyzed the main classifications of GSCC cases and compared their characteristics. It is clear that to have an appropriate definition of GSCC, well-defined diagnostic criteria are needed. Currently, there is no consensus. For practical purposes, it would be better to include a panel of CK and p40 to distinguish GSCC from adenocarcinoma. A GSCC outside the mucosa is not rare and could be a true entity.